Ja aber – Korpusbasierte Beobachtungen zu einer pragmatisch beschreibbaren Konstruktion - Staffeldt, Sven (Linguistik Online, 2018)
In spoken conversation as well as in written texts we can find examples of a construction which has been the object of linguistic research for about 35 years and which has repeatedly been described under the names of ja-aber syntagma, ja-aber connection and ja-aber utterance pattern. In most analyses this construction is split into two parts: The ja-part is seen to convey (partial) consent, whereas the function of the aber-part is interpreted as (partial) objection. Falling back upon ja as affirmative response particle and aber as adversative conjunction, such analyses operate on semantically compositional principles. Additionally, the possibility of ja being a structuring particle is taken into consideration, where ja is supposed to ensure the mere connection of the part following the particle with the antecedent part. However, as this paper wants to show, compositional approaches like these tend to mislead studies to circular lines of arguments, in which presumptive findings are taken for presuppositions (petitio principii). Moreover, they seem to disregard actual usage of this construction, which can be ascertained with the help of corpora. Corpus-aided investigation of the construction in question shows that its semantic elaboration is dependent on two factors that go beyond compositional explanation attempts: (1) syntactical integration of the aber-part and (2) presence of negation in the aber-part. Not even in “classic” examples this construction can be semantically reduced to simple combinations of consent + objection, though. In order to reach appropriate results here, semantic analysis has to turn to pragmatically more adequate ways of description.